Procedimientos metodológicos para desarrollar las habilidades intelectuales en el décimo año de educación básica del colegio "Kléber Franco Cruz", sección vespertina año lectivo 2004-2005. - Titinizhañay Saravia, Digna America (2005)
Intellectual skills allow us to understand ideas, processes, phenomena relations, etc., it is an understanding that arise from know-how, is an act one know how to handle yourself a leave traces in others a desire to transform the world.